2018
DOI: 10.2147/hmer.s158053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sitagliptin on hepatic histological activity and fibrosis of nonalcoholic steatohepatitis patients: a 1-year randomized control trial

Abstract: Background/purposeDipeptidyl peptidase 4 (DPP-4) expression is directly associated with hepatic lipogenesis and liver injury in nonalcoholic steatohepatitis (NASH). This study has been designed to elucidate the histological improvement of NASH with the DPP-4 inhibitor sitagliptin.Materials and methodsIn this open-label randomized control trial, paired liver biopsy was taken from 40 NASH patients. Sitagliptin 100 mg was given once daily to the SL group and no sitagliptin was given to the L group for 1 year. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 29 publications
4
65
1
4
Order By: Relevance
“…DPP4 inhibitors are also widely used diabetes drugs worldwide. Interestingly, there are currently clinical trials evaluating the efficacy and safety of DPP4 inhibitor sitagliptin for the treatment of NAFLD (Fukuhara et al , ) and in steatosis irrespective of diabetes in NASH (Alam et al , ). Taken together with our proteomic data, it would be interesting to further investigate the potential of circulating DPP4 levels to serve as prognostic marker for both T2D and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…DPP4 inhibitors are also widely used diabetes drugs worldwide. Interestingly, there are currently clinical trials evaluating the efficacy and safety of DPP4 inhibitor sitagliptin for the treatment of NAFLD (Fukuhara et al , ) and in steatosis irrespective of diabetes in NASH (Alam et al , ). Taken together with our proteomic data, it would be interesting to further investigate the potential of circulating DPP4 levels to serve as prognostic marker for both T2D and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Several uncontrolled studies have reported that treatment with DPP-IV inhibitors lowers plasma aminotransferase levels. [155][156][157][158][159][160][161] In one study, a lower plasma ALT was only observed in those with the most uncontrolled diabetes at baseline. 162 Kato et al 163 observed that while sitagliptin reduced IHTG compared to glimepiride, this was also associated with significant weight loss, possibly from concomitant lifestyle changes.…”
Section: Lactate Amino Acidsmentioning
confidence: 96%
“…In open-label prospective trials, sitagliptin has been found to improve plasma aminotransferases, (12,13) IHTG, (14) and liver histology. (15) But negative results have also been reported with sitagliptin in open-label studies (16,17) and in all three placebo-controlled trials. (18)(19)(20) Negative studies have been also reported with liraglutide, (20,21) but most have been positive with an improvement in hepatic steatosis (HS) (22)(23)(24)(25)(26)(27)(28) or liver histology.…”
Section: See Article On Page 2414mentioning
confidence: 98%
“…In animal models of NAFLD, both glucagon‐like peptide‐1 receptor agonists (GLP‐1Ras) and dipeptidyl peptidase‐4 inhibitor (DPP‐IVi) improve many pathways linked to steatohepatitis, although their efficacy at the clinical level has been mixed (see Tables and ). In open‐label prospective trials, sitagliptin has been found to improve plasma aminotransferases, IHTG, and liver histology . But negative results have also been reported with sitagliptin in open‐label studies and in all three placebo‐controlled trials .…”
Section: Effect Of Sitagliptin In Nafldmentioning
confidence: 99%